2012
DOI: 10.1371/journal.pone.0035069
|View full text |Cite
|
Sign up to set email alerts
|

Apilimod Inhibits the Production of IL-12 and IL-23 and Reduces Dendritic Cell Infiltration in Psoriasis

Abstract: Psoriasis is characterized by hyperplasia of the epidermis and infiltration of leukocytes into both the dermis and epidermis. IL-23, a key cytokine that induces T H 17 cells, has been found to play a critical role in the pathogenesis of psoriasis. Apilimod is a small-molecule compound that selectively suppresses synthesis of IL-12 and IL-23. An open-label clinical study of oral administration of apilimod was conducted in patients with psoriasis. Substantial improvements in histology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 43 publications
4
59
0
1
Order By: Relevance
“…In this study, we have identified Langerin neg cDCs as the critical pathogenic DC population initiating psoriatic plaque formation in mice via production of IL-23. To this end, our data extend previous findings and provide a functional rational to interfere with IL-23 activity or production using, for example, Ustekinumab, Fumarate, or Apilimod (37)(38)(39). Moreover, our work suggests that future strategies specifically blocking IL-23 secretion by Langerin neg cDCs may provide an effective treatment for psoriasis avoiding the problems associated with the general immunosuppression seen in many therapeutic approaches today.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we have identified Langerin neg cDCs as the critical pathogenic DC population initiating psoriatic plaque formation in mice via production of IL-23. To this end, our data extend previous findings and provide a functional rational to interfere with IL-23 activity or production using, for example, Ustekinumab, Fumarate, or Apilimod (37)(38)(39). Moreover, our work suggests that future strategies specifically blocking IL-23 secretion by Langerin neg cDCs may provide an effective treatment for psoriasis avoiding the problems associated with the general immunosuppression seen in many therapeutic approaches today.…”
Section: Discussionsupporting
confidence: 83%
“…PIKfyve-mediated PI(3,5)P 2 signaling has been shown to play a critical role in multiple biological processes by regulating endosomal trafficking, such as GLUT4 translocation, retroviral budding (12,13), autophagy (14), and neurodegeneration. Recently, we revealed that PIKfyve is the molecular target of apilimod (15), which is the first clinically evaluated small-molecule IL-12/IL-23 antagonist (16,17). We have shown that apilimod specifically binds to PIKfyve and inhibits its activity, which in turn silences TLR-induced IL-12/IL-23 production.…”
mentioning
confidence: 99%
“…Apilimod which selectively suppresses the synthesis of IL-12 and IL-23 by impairing the nuclear accumulation of c-Rel is in clinical studies for psoriasis, Crohn's disease and RA [13,137].…”
Section: Molecular Strategies To Block Il-23 Receptor Complex Assemblymentioning
confidence: 99%